Bacterial Expression of Biologically Active High Molecular Weight Kininogen Light Chain - Kunapuli, Satya P; DeLa Cadena, Raul A; Colman, Robert W (Thrombosis and Haemostasis, 1992)
Human high molecular weight kininogen (HK), a single chain plasma glycoprotein, serves as a cofactor in the contact system of blood coagulation. After cleavage by human plasma kallikrein, the nonapeptide bradykinin is released. The HK light chain (LC) contains coagulant activity, which requires both the ability to bind the contact system zymogens, prekallikrein and factor XI, and the ability to interact with negatively charged surfaces. Since bacterial expression might not be successful if carbohydrate was required for activity, we evaluated that possibility by incubating plasma HK with endoglycosydase F. Although the procedure removed detectable N-linked carbohydrate, no change in specific activity occurred. We then developed a bacterial expression system to produce recombinant HK LC. The cDNA coding for the HK LC was prepared by polymerase chain reaction (PCR), digested with restriction enzymes EcoRI and PstI, and introduced into the bacterial expression vector pKK223-3. E. coli harboring this recombinant plasmid (pSKl) expressed HK LC upon induction with isopropylthio-galactoside (IPTG). The recombinant protein (27 kDa), when transferred onto a PVDF membrane, was recognized by monospecific polyclonal anti-HK LC-antibodies. The recombinant HK LC was purified by heparin agarose affinity chromatography to homogeneity and found to have a specific activity of 28 coagulant units per mg protein, similar to the specific activity of the LC derived by proteolytic digestion of human plasma HK. We conclude: 1) The HK LC synthesized in bacteria is biologically active, and 2) the 40% carbohydrate content of the HK LC is not required for its cofactor activity.